Pemanfaatan Internet Sebagai Sumber Belajar Pada SMU Negeri 2 Pematangsiantar - Sundari Retno Andani; Poningsih (JPM: Jurnal Pengabdian Masyarakat, 2021)
The learning process today is inseparable from the use of technology as a learning resource. The internet as a medium of information that is able to penetrate the boundaries of space and time has a lot of potential that can support a better educational process. The amount of information available can be used as literature to broaden horizons. Utilization of the internet as a learning medium is one component of learning resources and at the same time a form of problem solving learning that can be considered as a new thing. This phenomenon is expected to be a solution to the problems that have occurred so far, such as limited manpower, distance, geographical location, high costs and limited study time.